First report of the female of Cheirochela assamensis Hope, 1841 (Hemiptera: Heteroptera: Naucoridae) from northeastern India - Shruti V. Paripatyadar; Sophio Riphung; Hemant V. Ghate (Journal of Threatened Taxa, 2015)
This publication reports for the first time the female of a Naucorid Bug Cheirochela assamensis Hope, 1841 from the state of Meghalaya, India.  This species has been known so far by only two male specimens.  We provide a detailed description of the female and light microscopic images of the habitus and important characters.  Habitus photos of type (male) of C. assamensis and a related species, Cheirochela thailandana Polhemus et al. are also provided for comparison.